Evaluation of the Singapore Emergency Medical Team (SGEMT) Hybrid Training Course and Its Field Impact During the Mandalay Earthquake Relief Mission Using the Kirkpatrick Framework - Rejap, Nurul Ain Binte; Heng, John Low Zhong; Jiayi, Alexa Zeng; Hui, Ng Min; Hong, Goh Ying; Jamil, Ahmad Khairil Bin Mohamed; Joy, Quah Li Juan; Ho, Shu Fang (Universitas Gadjah Mada, 2026)
Introduction: Effective pre-deployment training enables disaster relief medical teams to operate safely and efficiently in resource-limited environments. Objective: This study evaluates the effectiveness of the Singapore Emergency Medical Team (SGEMT) Hybrid Training Course in preparing personnel for WHO Type 1 (Fixed) EMT accreditation and subsequent deployment to Mandalay following a major earthquake. Methods: Training outcomes were assessed using the Kirkpatrick four-level evaluation model, which included post-training surveys, training completion records, thematic analysis of free-text responses, WHO EMT classification exercise, deployment operational metrics and post-deployment evaluation. Results: Participants reported high satisfaction and perceived role relevance (Kirkpatrick-Level-1) Thematic analysis revealed enhanced confidence and operational preparedness (Kirkpatrick-Level-2). After attaining WHO EMT accreditation, SGEMT underwent its first deployment, treating 1,803 patients over eight days, including 33 high-acuity cases with no adverse events (Kirkpatrick-Levels-3-and-4). Key program enablers were realistic scenarios conducted in a collaborative learning environment that reinforced technical and non-technical skills such as team collaboration, open communication, and psychological resilience. Conclusion: The SGEMT Hybrid Training Course helped foster individual and team competencies, which supported effective real-world disaster response. This study provides evidence supporting a multi-component, team-based training model grounded in adult learning principles and offers a practical framework for evaluating EMT training programs